2008
DOI: 10.1111/j.1755-618x.2008.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Work Intensification and Educational Contradictions in Aboriginal Communities

Abstract: L'auteur se penche sur l'évolution de la nature professionnelle de l'enseignement en relation avec les initiatives pour améliorer l'éducation chez les autochtones. Il examine les répercussions de plusieurs courants potentiellement contradictoires de réforme éducationnelle. Ceux-ci contiennent en particulier des préoccupations concernant l'augmentation de la tâche des enseignants, la restauration professionnelle de l'enseignement, afin de satisfaire les besoins des sociétés fondées sur le savoir, et leurs consé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Furthermore, non-Indigenous students may still go through their entire educational career without learning about Indigenous Peoples and the history and legacy of residential schooling in Canada. Wotherspoon (2006Wotherspoon ( , 2008 also found that educators had varying responses to Indigenous oriented schooling reform. While some educators increased sensitivity to Indigenous students and wanted to implement change in curriculum content and instructional methods, other educators remained fixated on teaching their subject along a universal standard curriculum mandate and believed that all students should be treated the same (see also St.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, non-Indigenous students may still go through their entire educational career without learning about Indigenous Peoples and the history and legacy of residential schooling in Canada. Wotherspoon (2006Wotherspoon ( , 2008 also found that educators had varying responses to Indigenous oriented schooling reform. While some educators increased sensitivity to Indigenous students and wanted to implement change in curriculum content and instructional methods, other educators remained fixated on teaching their subject along a universal standard curriculum mandate and believed that all students should be treated the same (see also St.…”
Section: Discussionmentioning
confidence: 99%
“…Indigenous curricular content as well as traditional Indigenous methods of teaching and learning are also seen to contribute to Indigenous student self-confidence, self-esteem, and cultural identity (McDonald, 2011;Taylor & Wright, 2003). There is reason to believe, however, that due to various environmental pressures educator practices may be inconsistent with Indigenous curricular policies, preventing substantial change at the level of teaching and learning (Labaree, 2010;Wotherspoon, 2006Wotherspoon, , 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As progress is made to address these concerns, several obstacles remain. Educators committed to changing pedagogical practices and incorporating curricular content that acknowledges Indigenous cultural heritage and learning contexts often lack the knowledge, confidence, or support to do so effectively (Canadian Teachers' Federation [CTF], 2015;Milne, 2017;People for Education, 2017;Wotherspoon, 2006Wotherspoon, , 2008. An Ontario study revealed that educators sometimes have limited knowledge about official Indigenous curricular policy documents and directives, while others have difficulty finding, interpreting, and using resources to the extent that non-Indigenous students sometimes "go through their entire educational career without learning about Indigenous Peoples and the history and legacy of residential schooling in Canada" (Milne, 2017, p. 10).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature that addressed teachers" work and lives, there is abundant evidence of the detrimental impact of the intensification of teachers" work on teachers" professional identity, moral purpose, and desire to remain in teaching (e.g. Merson, 2000;Penrice, 2011;Wotherspoon, 2008;Roberts-Holmes, 2003;Smethem, 2007). Although my research offers some support to these findings, as the discussion of the results in the above shows, there also seems to be some differences.…”
Section: A Influences Of Intensification On Teachers' Identitiesmentioning
confidence: 58%